Demospongiae of ANT XXIV/2 (SYSTCO I) Expedition—Antarctic Eastern Weddell Sea - Göcke, Christian; Janussen, Dorte (Zootaxa, 2013)
In this study, we present the demosponges sampled in the Antarctic Weddell Sea during the ANT-XXIV/2 (SYSTCO I) expedition (28.11.2007–04.02.2008) by the RV Polarstern. This collection comprises 43 species of Demospongiae of which four species are new to science, three of which are described herein, Cornulum antarcticum sp. nov., Cladorhiza penniformis sp. nov., and Desmacella koltuni sp. nov. We furthermore provide short descriptions and remarks for all species found, and in cases of rare or badly characterized species we also provide detailed documentation and descriptions of our material. In conclusion, we discuss the comparative faunistic and ecological aspects of our collection with respect to the Weddell Sea sponge fauna.